Fractal hydrological-thermal–mechanical analysis of unconventional reservoir: A fracture-matrix structure model for gas extraction. (March 2023) - Ye, Dayu; Liu, Guannan; Wang, Fangtian; Gao, Feng; Yang, Tingting; Zhu, Jingyun
Highlights: New coupling relationship of fracture-matrix microstructure and macroscopic behavior of unconventional reservoir is proposed. A new cross-scale coupled hydrological-thermal–mechanical fractal seepage model is developed. The contribution of the reservoir microstructure to extraction process under multi-physical field effects is investigated. The impacts of the macroscopic behavior on the microstructure is analyzed. Permeability of unconventional reservoir is enhanced by 9.45–86.74% compared to the cubic permeability model. Abstract: The complex fracture-matrix structure of the unconventional reservoir will significantly affect the gas seepage, energy conduction and the extraction properties. A good understanding of the underlying mechanisms controlling such a process is essential for a clear description of the reservoir gas extraction problems. In this study, we propose a fractal dual-porosity permeability model through analytical derivation, and the fracture-matrix microstructural properties of the reservoir is characterized by the following structural parameters: (1) density of natural fractures ( Df ), (2) density of matrix pores ( Dp ), (3) maximum natural fracture length ( lmax ), and (4) maximum matrix pore radius ( λmax ). These structural parameters evolve with the effective stress through porosity under the combination of hydrological-thermal–mechanical interactions, reservoir deformation, fracture-matrix interactions, and gas adsorption-desorption effect. The results indicate that: (1) the fractal model proposed in this paper is capable of better characterizing the reservoir microstructure at the fracture-matrix scale compared with the homogeneous models (9.45 and 78.07% enhancement in permeability of the fracture system whilst 10.46% and 86.74% enhancement in permeability of the matrix system); (2) the effective stress due to the evolution of microstructure has a significant contribution to reservoir temperature and gas pressure; (3) adsorption-desorption and thermal expansion effects dominate the unconventional reservoir structure; (4) greater initial pressure causes clearer effect on the overall fracture-matrix structure. This study might shed light on the investigation of the gas seepage property and improve the recovery of the unconventional reservoir.